Zakat houses for asnaf faqr and miskin: are houses appropriate and adequate? - Abdul Rashid, Khairuddin; Ahmad Sarkawi, Azila; Hasan, Sharina Farihah; Aripin, Srazali (Faculty of Economics, Sultan Agung Islamic University, 2015)
Among the assistance provided by zakat administrators in Malaysia is the provision of shelter or housing for asnaf fakr and miskin. Under this form of assistance, asnaf fakr and miskin are given monetary assistance either to build new houses (for those that own land), to repair current houses or to help in meeting the cost of rental charges. However, there is no published literature to describe the specifications of the new houses or the state and conditions of such houses and houses repaired or rented. Consequently, a study was carried out. The key objectives of the study are to identify and ascertain whether the houses, either newly-built, newly repaired or rented on behalf of the asnaf fakr and miskin are appropriate and adequate in terms of their size, location, provision of basic utilities and facilities, their surrounding environments, etc. and in terms of meeting the requirements of the shari’ah in its design and in other aspects such as privacy and gender segregation of the households. The study involved review of related literature and case studies on houses that are currently being funded – newly built, repaired and rented – by selected zakat authorities. Data obtained from the case studies is then contrasted with data on standards of housing that are deemed to be appropriate for asnaf fakr and miskin. Key findings from the study suggest that the houses currently being funded by the selected zakat authorities are neither appropriate nor adequate in terms of meeting the needs and requirements of the households of the asnaf fakr and miskin. As a way forward, zakat administrators are recommended to make reference to currently available standards when considering funding newly built houses, repair of existing houses or renting houses for asnaf fakr and miskin. In the longer term, zakat administrators should consider designing their own and shari’ah compliant standards for zakat funded housing for the asnafs.